2014
DOI: 10.1063/1.4903970
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent scale interactions in the far-field of a turbulent mixing layer

Abstract: 13.04.15 Kb. Ok to add accepted version to spira

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
4
11
0
Order By: Relevance
“…The data are identical to that used by Buxton et al (2011) in the developed, far field region of a turbulent planar mixing layer that closely matches the experimental dataset of Buxton & Ganapathisubramani (2014). The mixing layer is produced by means of a DNS of two flows of different free stream velocities, U 1 and U 2 in the ratio U 1 /U 2 = 2, either side of a splitter plate of thickness h to which a wedge of angle 4…”
Section: Datamentioning
confidence: 66%
See 4 more Smart Citations
“…The data are identical to that used by Buxton et al (2011) in the developed, far field region of a turbulent planar mixing layer that closely matches the experimental dataset of Buxton & Ganapathisubramani (2014). The mixing layer is produced by means of a DNS of two flows of different free stream velocities, U 1 and U 2 in the ratio U 1 /U 2 = 2, either side of a splitter plate of thickness h to which a wedge of angle 4…”
Section: Datamentioning
confidence: 66%
“…This is a measure that quantifies the loss of information in modelling a statistical distribution of small-scale quantities conditioned on concurrent positive large-scale fluctuations by that conditioned on negative large-scale fluctuations. It is observed that the small-scale turbulence is appreciably "rougher" when the concurrent large-scale fluctuation is positive in the low-speed side of a fully developed turbulent mixing layer which lends further evidence to the convective scale modulation argument of Buxton & Ganapathisubramani (2014). The definition of the small scales is varied and regardless of whether the small-scale fluctuations are dominated by dissipation or have the characteristic features of inertial range turbulence they are shown to be modulated by the concurrent large-scale fluctuations.…”
mentioning
confidence: 84%
See 3 more Smart Citations